Impact of Intermittent Fasting on Human Endocrine and Metabolic Physiology: A Systematic Review: Intermittent Fasting on Human Endocrine and Metabolic Physiology - Tirimzi, Syed Soban Ahmed; Khalid, Maham; Shuaib, Ambar; Aziz, Asma; Riaz, Ayesha; Aslam, Misbah (Pakistan Journal of Health Sciences, 2026)
Intermittent fasting (IF) is increasingly recognized as a dietary approach that may improve endocrine and cardiometabolic health by aligning eating patterns with circadian rhythms. Objectives: To systematically evaluate recent human studies (2018–2024) investigating the effects of intermittent fasting on endocrine and metabolic physiology, with emphasis on insulin sensitivity, hormonal balance, and cardiometabolic outcomes. Methods: PubMed, Scopus, and the Cochrane Library were searched according to PRISMA 2020 guidelines. Randomized controlled, crossover, cohort, and observational studies reporting endocrine (insulin, leptin, ghrelin, cortisol) and metabolic (glucose, lipids, body composition) outcomes associated with intermittent fasting were included. Study quality was assessed using the Joanna Briggs Institute tools. Results: Eighteen studies (~1,250 participants) were included. Early time-restricted eating and alternate-day fasting were consistently associated with improved insulin sensitivity, glycemic control, lipid profiles, and blood pressure. Several trials reported endocrine benefits independent of major weight loss. Most randomized studies showed low risk of bias. Conclusions: Low-risk randomized evidence supports early time-restricted eating and alternate-day fasting as effective strategies for improving insulin sensitivity and glycemic control. Other hormonal outcomes remain associative and require further trials. Intermittent fasting is a promising, culturally adaptable approach for metabolic risk reduction.